# math

posted by .

combine like terms

18x^4+2x^3y^3-1-2y^3-17x^4=

• math -

18x^4+2x^3(y^3)-1-2y^3-17x^4=

x^4 + 2x^3 (y^3) - 2y^3 - 1 =

x^4 + 2x^3 (y^3) - 2y^3 - 1 =

x^4 + 2y^3 (x^3 - 1) - 1

This should be it, unless the parentheses are differently arranged.

I hope this helps. Thanks for asking.

## Similar Questions

1. ### polynomials

(3+7x)-(16x2+15x2) (3+1x)-(12x+16+0+18x2) Q4: (15+13x2+14x2)+(13x+18x) Q5: (2x2+1+15x2+7+3)+(0x+17x) Q6: (18x+3)+(17x2+1x2+9+8+0x) Q7: (6x + 14) - (9x + 5) Q8: (14x2 + 13x + 12) - (7x2 + 20x + 4) Q9: Subtract -10x2 + 16x - 15 from …
2. ### polynomials

(3+7x)-(16x2+15x2) (3+1x)-(12x+16+0+18x2) Q4: (15+13x2+14x2)+(13x+18x) Q5: (2x2+1+15x2+7+3)+(0x+17x) Q6: (18x+3)+(17x2+1x2+9+8+0x) Q7: (6x + 14) - (9x + 5) Q8: (14x2 + 13x + 12) - (7x2 + 20x + 4) Q9: Subtract -10x2 + 16x - 15 from …
3. ### math

I believe Lance meant to write x = -5/18 I am wondering why you have two minus signs before the number 13. Two minuses make a plus, but usually they are not written that way. combine like terms -18x=5 solve for x x=5/18 what does x …

x-2 6x ____ - _____ 3x+4 x+1 *You are supposed to simplify the expresion.I really need help with this and some other problems.Please and Thank you.- Perhaps I could help but I can't make heads or tails of your posts. Try using parentheses …
5. ### BobPursley..here it is:

Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common denominator is: (3x+4)(x+1) (x-2)(x+1)/(3x+4)(x+1) - 6x(3x+4)/(x+1)(3x+4) [(x-2)(x+1) - 6x(3x+4)] / (x+1)(3x+4) (x^2 - x - 2 - 18x^2 - 24x) / (x+1)(3x+4) x^2 - 18x^2 = -17x^2 -x …
6. ### Algebra

2(3x - 7) + 4 (3 x + 2) = 6 (5 x + 9 ) + 3 how will solve it?
7. ### Algebra

(x)/(x-3)-4-(2x-5)/(x+2) I posted something before this, so now this is how far I got. The answer I know is -(5x^2-17x-9)/(x-3)(x+2) first I get (x)(x+2)/(x-3)(x+2)- (4)(x-3)(x+2)/(x-3)(x+2)-(2x-5)(x-3)/(x-3)(x+2) Then I get x^2+2x-4x^2-4x-24-2x^2-11x+15 …
8. ### Algebra

(x)/(x-3)-4-(2x-5)/(x+2) I posted something before this, so now this is how far I got. The answer I know is -(5x^2-17x-9)/(x-3)(x+2) first I get (x)(x+2)/(x-3)(x+2)- (4)(x-3)(x+2)/(x-3)(x+2)-(2x-5)(x-3)/(x-3)(x+2) Then I get x^2+2x-4x^2-4x-24-2x^2-11x+15 …
9. ### math

could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17
10. ### math

could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17

More Similar Questions